Kemampuan siswa SD dalam berpikir kreatif matematis untuk menyelesaikan soal open-ended - Situmorang, Raja Uruk; Rufiana, Intan Sari; Rahayuningsih, Sri; Dewi, Radeni Sukma Indra; Arifin, Slamet (IKIP Siliwangi, 2025)
Mathematical creative thinking skills are essential competencies that need to be developed in students. This study aims to analyze students' mathematical creative thinking abilities in solving open-ended problems based on Silver’s indicators. A descriptive qualitative approach was used, involving fifth-grade students from SD Bruder Melati, categorized by their level of ability high, medium, and low. Data were collected through written tests (open-ended questions), interviews, and observations. The data analysis involved data reduction, data presentation, and drawing conclusions. The results showed that the fluency aspect had the highest percentage, followed by flexibility and originality. High-ability students were more confident in trying various problem-solving strategies and demonstrated better thinking flexibility. Medium-ability students tended to rely on known patterns before attempting their own alternatives, while low-ability students struggled with all aspects of creative thinking. The findings suggest that while students are capable of generating multiple solutions, they still face challenges in applying diverse strategies and producing unique solutions.